Nous sommes tous des féministes - Adichie, Chimamanda Ngozi (Gallimard, 2020)
Dans le premier texte, à l'origine un discours prononcé en 2012 dans le cadre d'un programme dédié à l'essor du continent africain, l'écrivaine nigériane aborde avec lucidité et humour le sujet du féminisme. A travers des anecdotes issues de sa vie quotidienne, au Nigeria comme aux Etats-Unis, elle évoque les questions de l'inégalité des sexes et de l'image de soi des femmes.
Keywords: afrique; afro-féminisme; amériques; approches et analyses; cours; cycles supérieurs; droits des femmes*; fem7000; féminismes noirs; inégalités; lit3220; nigeria; premier cycle; rapports sociaux de sexe; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*; états-unis

The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis